Complete mitochondrial genome of the clearwing moth Synanthedon bicingulata (Lepidoptera: Sesiidae) - Woo Jin Kim; Seung Hyun Lee; Jeong Sun Park; Iksoo Kim (Mitochondrial DNA. Part B. Resources)
The clearwing moth, Synanthedon bicingulata Staudinger, 1887 (Lepidoptera: Sesiidae), is a serious pest that infests cherry trees. This species, which is distributed in South Korea, was once regarded as S. hector found in Japan, but renamed as S. bicingulata based on morphology. Molecular data for this species are not available. Hence, we sequenced the 16,255-bp long complete mitochondrial genome (mitogenome) of S. bicingulata. Phylogenetic analyses in the Cossoidea superfamily supported monophyly of the Synanthedon genus and Synanthedonini tribe. This newly sequenced mitogenome of S. bicingulata will be useful for studies in a diverse field of evolutionary study.